2004
DOI: 10.1063/1.1651052
|View full text |Cite
|
Sign up to set email alerts
|

Size and persistence length of molecular bottle-brushes by Monte Carlo simulations

Abstract: Single-chain simulations of densely branched comb polymers, or "molecular bottle-brushes" with side-chains attached to every (or every second) backbone monomer, were carried out by off-lattice Monte Carlo technique. A coarse-grained model, described by hard spheres connected by harmonic springs, was employed. Backbone lengths of up to 100 units were considered, and compared with the corresponding linear chains. The backbone molecular size was investigated as a function of its length at fixed arm size, and as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
112
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(119 citation statements)
references
References 36 publications
7
112
0
Order By: Relevance
“…Methanol molecules have both hydrophilic hydroxyl groups and hydrophobic methyl groups; therefore, the PTrEGS polymers can also be easily dissolved in methanol. Figure 2 shows the SANS data of 1.0 wt % polymers with DP ) 85 in toluene-d 8 26 suggests that the interactions between the polymers in this solvent are attractive, and this is attributed to insolubility of hydrophobic PS backbones in water. Individual homopolymers such as PS are known to collapse into globules in poor solvents, and the globules tend to form clusters because of attractive interactions between polymer segments.…”
Section: Solvent Quality For Ptregs With a Dp Of 85mentioning
confidence: 99%
See 2 more Smart Citations
“…Methanol molecules have both hydrophilic hydroxyl groups and hydrophobic methyl groups; therefore, the PTrEGS polymers can also be easily dissolved in methanol. Figure 2 shows the SANS data of 1.0 wt % polymers with DP ) 85 in toluene-d 8 26 suggests that the interactions between the polymers in this solvent are attractive, and this is attributed to insolubility of hydrophobic PS backbones in water. Individual homopolymers such as PS are known to collapse into globules in poor solvents, and the globules tend to form clusters because of attractive interactions between polymer segments.…”
Section: Solvent Quality For Ptregs With a Dp Of 85mentioning
confidence: 99%
“…The nearly zero A 2 suggests that the solubility of the polymers in methanol is between toluene and D 2 O. The molecular weight of the polymer, M w , determined from Zimm plots in toluene-d 8 (27 800 g/mol), methanol-d 4 (39 600 g/mol), and in D 2 O (29 000 g/mol) agrees within 20% with the M w measured using gel permeation chromatography (34 800 g/mol). For the sake of clarity, the data of the toluene solutions were shifted by a factor of 1.2, 4, 8, 14, and 24 for the polymers of DP ) 8, 40, 47, 58, and 85, respectively.…”
Section: Solvent Quality For Ptregs With a Dp Of 85mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it has recently been shown that the persistence length depends not onlyon the backbone length [19,20], but on the solvent conditions as well [15]. Although there exist many experimental and theoretical studies for the linear d imensions of these macro molecules in various solvents [3,4,19,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36],there are very few systematic studies of this problem [15], wherethe power laws and the associated effective exponents have been with a Flexible Backbone under Theta and Good Solvent Conditions discussed.It has been shown that for bottle brushes with a flexib le backbone evenat the theta point the side chains are considerably stretched,their linear dimension depending on the solvent quality only weakly, whilethe dependence of the persistence length on backbone length and temperature has alsobeen discussed [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, computer simulations have been very useful to validate approximations needed to interpret experimental data [10,12,16,17,18,19,20,21,22,23,24,25,26]. Since some of the suggested applications require to consider bottle-brush polymers under poor solvent conditions, first steps to consider this case by theory [27] and simulations [28,29,30] have been taken.…”
Section: Introductionmentioning
confidence: 99%